Pontoppidan som nøgle til kontroversielle emner i danskfaget - Prætorius, Lotte (Pontoppidaniana, 2025)
Abstract This article explores how the literature of Henrik Pontoppidan can be used in the classroom to facilitate discussions on controversial topics. Research indicates that educators often avoid such subjects due to concerns about student wellbeing and potential classroom conflict. Teaching controversial issues requires a delicate balance, fostering open dialogue and reflection without predetermined answers, allowing students to seek understanding through debate. Literature offers a valuable tool in this context, providing language for difficult conversations. Pontoppidan’s works address themes such as antisemitism, oppression, and suicidal thoughts, presenting characters’ disillusionment and despair. These portrayals create both a mirror and a safe distance for students to engage with complex and sensitive issues.